Partisipasi Politik Penerima Manfaat Penyandang Disabilitas Program Keluarga Harapan Pada Pemilihan Legislatif 2019 - Nina Oktapiani; Warjio Warjio; Bengkel Ginting (PERSPEKTIF, 2022)
The purpose of this article is to analyze the low level of political participation of PKH Beneficiary Families with disabilities in the 2019 Langkat Regency Legislative Election and what are the factors behind the low political participation of PKH Beneficiary Families with disabilities in the 2019 Langkat Regency Legislative Election. This research method is descriptive qualitative, by presenting the facts found comprehensively through in-depth analysis. While the data analysis technique consists of data reduction, data presentation and drawing conclusions. The results of the study showed that there were still many KPMs with disabilities who did not participate in the election, only 5 KPMs with disabilities took part in the 2019 legislative elections out of 13 KPMs with disabilities who met the requirements. The factor that causes it is minimal accessibility from both the organizers and the family, including not being registered in the DPT (permanent voter list) because it is not listed in the KK.